β-Galactosidase-Producing Isolates in Mucoromycota: Screening, Enzyme Production, and Applications for Functional Oligosaccharide Synthesis - Bettina Volford; Mónika Varga; András Szekeres; Alexandra Kotogán; Gábor Nagy; Csaba Vágvölgyi; Tamás Papp; Miklós Takó (Journal of Fungi, 2021)
β-Galactosidases of Mucoromycota are rarely studied, although this group of filamentous fungi is an excellent source of many industrial enzymes. In this study, 99 isolates from the genera Lichtheimia, Mortierella, Mucor, Rhizomucor, Rhizopus and Umbelopsis, were screened for their β-galactosidase activity using a chromogenic agar approach. Ten isolates from the best producers were selected, and the activity was further investigated in submerged (SmF) and solid-state (SSF) fermentation systems containing lactose and/or wheat bran substrates as enzyme production inducers. Wheat bran proved to be efficient for the enzyme production under both SmF and SSF conditions, giving maximum specific activity yields from 32 to 12,064 U/mg protein and from 783 to 22,720 U/mg protein, respectively. Oligosaccharide synthesis tests revealed the suitability of crude β-galactosidases from Lichtheimia ramosa Szeged Microbiological Collection (SZMC) 11360 and Rhizomucor pusillus SZMC 11025 to catalyze transgalactosylation reactions. In addition, the crude enzyme extracts had transfructosylation activity, resulting in the formation of fructo-oligosaccharide molecules in a sucrose-containing environment. The maximal oligosaccharide concentration varied between 0.0158 and 2.236 g/L depending on the crude enzyme and the initial material. Some oligosaccharide-enriched mixtures supported the growth of probiotics, indicating the potential of the studied enzyme extracts in future prebiotic synthesis processes.